how do i evaluate the following two expressions??

9 8 2 - 3 / +

I come up with

9 - 8 = 1 / 2 = .5 + 3 = 3.5

3 4 5 2 * - +

I come up with

3 * 4 = 12 - 5 = 7 + 2 = 9

Am I doing this right when talking of binary tree postfix expressions???

Printable View

- 12-11-2001Unregisteredpostfix expressions
how do i evaluate the following two expressions??

9 8 2 - 3 / +

I come up with

9 - 8 = 1 / 2 = .5 + 3 = 3.5

3 4 5 2 * - +

I come up with

3 * 4 = 12 - 5 = 7 + 2 = 9

Am I doing this right when talking of binary tree postfix expressions??? - 12-11-2001quzah
9 8 2 - 3 / +

Actually, I believe to be totally postfix, it would be:

9 8 2 3 / + -

Which would be:

9 - 8 = 1

1 / 2 = .5

.5 - 3 = -2.5

But I could be wrong. I've personally never had use for postfix notations.

Quzah. - 12-11-2001QuestionC
The best way to do this is just look at it one operator at a time...

First we just have some numbers...

9 8 2

then we get a '-', which operates on the last 2 values...

9 (8, 2)-

now, (8, 2)- is a value, that is, it represents 6. We could just replace (8, 2)- with 6 at this point, but I don't for the purpose of showing how postfix is changed to other forms.

another number....

9 (8, 2)- 3

and an operator that will work on the last 2 values

9 ((8, 2)-, 3)/

and another operator that will work on the last 2 values...

(9, ((8, 2)-, 3)/)+

Now we just break it down into infix using the parenthesis...

(9 + ((8 - 2) / 3))

And that's how you analyze it.

Or, just replacing the values, it would analyze like this...

9 8 2 - == 9 6

9 6 3 / == 9 2

9 2 + == 11

11 nothing left, so 11's the answer. - 12-12-2001Unregistered
so with your logic explained would the second expression i have

3 4 5 2 * - +

be.......

3, 4 (5,2) *

3,(4,(5,2)*)-

(3,(4,(5,2)*)-)+

(3 + (4 - (5*2))) = -3 - 12-12-2001QuestionC
Exactly.